Avaliação de alterações periodontais induzidas pelo aumento do tecido adiposo em camundongos - Marina Campos Zicker (2020)
Periodontal disease (PD) is an inflammatory condition of infectious etiology, which affects the supporting tissues of the teeth. Changes in oral microbiota homeostasis can trigger an exacerbated inflammatory response, which can lead to impairment of periodontal tissues. Obesity is a worldwide public health problem, associated with high consumption of fats and carbohydrates. Increased body fat tissue may contribute to the activation of the systemic inflammatory response, leading to comorbidities. Some studies have shown that obese patients have a higher incidence of PD than eutrophic. However, mechanisms are still unclear. It has been shown that increased adipose tissue can induce alveolar bone loss similar of what is observed in an experimental model of PD. Thus, this study aimed to investigate the mechanisms involved in alveolar bone loss induced by the increase in adipose tissue in mice, also assessing a role of the oral microbiota in this process. For this, mice were submitted to control or high fat (HF) diet. Leptin receptor-deficient mice (db/db - /- ) were also used. The results show that the increased adipose tissue, through HF diet or by genetic alteration, induced neutrophils recruitment and alveolar bone loss in mice, associated with a dysbiosis of the oral biofilm. The depletion of the oral microbiota by the use of CHX preserved the physiological bone conditions. Thus, the results show that changes in the oral microbiota and a neutrophilic infiltrate may play an important role in alveolar bone loss induced by the increase in adipose tissue.